Between magic and reason: science in 19th century popular fiction - Roach, Katherine (2011)
The scientist in fiction is much maligned. The mad, bad scientist has framed much of the debate about literary representations of science and with good reason since he is a towering icon of popular culture. Yet, I will propose that an equally preeminent figure provides an alternative model of science in fiction. This is the detective.